Implementation of an Electronic Health Record–Based Messaging System in the Emergency Department: Effects on Physician Workflow and Resident Burnout. Issue 2 (March 2022) - Luu, Tiffany; Spiegelman, Lindsey; Nykin, David; Abido, Kimberly; Roh, Jennifer; Rudkin, Scott; Toohey, Shannon
Abstract : Introduction: The traditional methods of communication between nurses and physicians through paging or phone calls have been known to cause patient care interruptions, increase stress and workload, and cause burnout. Our study assessed the impact of using an electronic health record–based messaging system (Epic Secure Chat) for nonemergent communication between nurses and physicians in the emergency department (ED). Method: This study was performed at a large urban academic ED. Surveys were distributed through e-mail using Google forms. Preimplementation and postimplementation surveys were performed from May 2019 (presurvey) to August 2019 (postsurvey). Result: The number of nonurgent phone calls from registered nurse staff decreased after intervention ( P < 0.001). The frequency of nonurgent calls disrupting workflow decreased after the intervention ( P = 0.029). The number of calls that were appropriately alerted to increased but was not significant ( P = 0.120), whereas the degree of burnout from nonurgent calls remained relatively the same ( P = 0.841). Conclusions: The findings provide insight into the implementation of an EMR messaging system in an ED setting. These findings suggest the messaging system can decrease unnecessary nonurgent calls from registered nurses and medical doctors, allowing for more efficient workflow in the ED. These findings suggest further research especially regarding burnout implemented on a larger scale and yield redesign suggestions in the ED.